A study to customize the methodology of engineering teaching based on the intelligence levels of students for better retention - Arul Kumar R, Joshua; Barnabas, A. (2012 IEEE International Conference on Engineering Education: Innovative Practices and Future Trends, 2012)
This paper deals with an analysis of a batch of engineering students of Electronics and Communication Engineering department and suggests ways of customizing Teaching by active learning process for effective learning. The basis for the analysis is taken by grouping the students based on their intelligences proposed by Howard Gardners Multiple Intelligence Theory. Then the methodologies of teaching that can be introduced for different classes of the department is proposed. A study of variation of intelligences as a whole class is analysed for a particular batch of students for over a period of time. The findings are presented and the reasons for the same are studied. Thus this paper identifies the use of different innovative methodologies of teaching at class room level to enable active learning in an effective way taking into consideration the needs of the learners. It aims at bringing a best possible learning outcome focusing on students retention of the subject.